Wind Speed Estimation Based Sensorless Output Control for A Wind Turbine Driving A DFIG (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A specific design of the proposed control algorithm for a wind turbine equipped with a doubly fed induction generator (DFIG) is presented. The aerodynamic characteristics of the wind turbine are approximated by a Gaussian radial basis function network based nonlinear input-output mapping. Based on this nonlinear mapping, the wind speed is estimated from the measured generator electrical output power while taking into account the power losses in the WTG and the dynamics of the WTG shaft system. The new control methodology means the fuzzy logic controller has been developed and evaluated in detail. Finally, the proposed method is applied to the wind generation system The estimated wind speed is then used to determine the optimal DFIG rotor speed command for maximum wind power extraction. The DFIG speed controller is suitably designed to effectively damp the low-frequency torsional oscillations. The resulting WTG system delivers maximum electrical power tothe grid with high efficiency and high reliability without mechanical anemometers.